Improving patient knowledge of palliative care: A randomized controlled intervention study. Issue 5 (May 2017) - Kozlov, Elissa; Reid, M. Carrington; Carpenter, Brian D.
Highlights: Laypersons' knowledge of palliative care can be improved with educational interventions. Both video and informational page interventions improve knowledge of palliative care. Educational interventions improve laypersons' confidence in their knowledge of palliative care. Abstract: Objectives: To determine if laypersons' knowledge about palliative care can improve with a brief education intervention. Methods: 152 adults were recruited to participate in a web-based randomized intervention trial that followed a 2 (content) × 2 (format) between-subjects design. Groups received either a video intervention, an information page intervention, a video control, or an information page control. An ANCOVA with contrast coding of two factors was utilized to assess if knowledge, as measured by the Palliative Care Knowledge Scale (PaCKS), increased post intervention. Results: There was a significant difference between intervention group means and control group means on PaCKS scores from T1 to T2 F (1, 139) = 11.10, p = 0.00, ηp 2 = 0.074. There was no significant difference in PaCKS change scores between the video intervention and information page intervention. Conclusions: This study demonstrates that an information page and a brief video can improve knowledge of palliative care in laypersons. Practice implications: Self-administered educational interventions could be made available in diverse settings in order to reach patients and their families who may benefit from but are unaware of palliative care. Interventions more intensive than the one tested in this study might result in even more significant improvements in knowledge.